A total reversal of the balance of power?: German prisoners of war in Normandy, 1944-1948 - Schneider, Valentin (2016)
This dissertation interrogates the relation between the French national identity, constructed around the idea of hereditary enmity with Germany, and the behaviour between French and German prisoners of war on the individual level in Normandy between 1944 and 1948. This question is important since it is widely accepted that Franco-German relations reached an all-time low during World War II, especially in areas like Normandy that had been heavily occupied between 1940 and 1944. This position is examined through an entangled analysis of low and high level records both from German and French sources, but also from American, British, and Swiss origins. It appears that individual Franco-German relations depended on the distance between the French official discourse of national recovery and the reality experienced by the civil population. During the Allied presence in Normandy, contradictions were obvious and the relations between French and German prisoners of war in Allied hands were marked with violence. When discourse and reality began to overlap, after the transfer of the prisoners to French custody, individual Franco-German relations normalised. This rapid evolution points to the symbolic character of the enmity between French and Germans, used as a tool to reinforce the national cohesion in times of threat.